Proton transfer reactions of a bridged bis‐propyl bis‐imidazolium salt†. (5th May 2016) - Massey, Richard S.; Quinn, Peter; Zhou, Shengze; Murphy, John A.; O'Donoghue, AnnMarie C.
Abstract : Tetraazafulvalene1 has found broad application in reduction and other related transformations and is conveniently generated from bis ‐propyl bis ‐imidazolium salt4 with a strong base in a non‐protic solvent. The proposed mechanism for the formation of1 involves initialdeprotonation at C(2) to give a mono‐carbene9 followed byintramolecular reaction at the second azolium centre. Herein, we report the second‐order rate constants for deuteroxide‐catalysed exchange in aqueous solution of the C(2)‐hydrogens of bis ‐propyl bis ‐imidazolium di‐iodide salt4 and related monomeric dipropyl imidazolium iodide10 of k DO = 1.37 × 10 4 and 1.79 × 10 2 M −1 s −1, respectively, and used these data to calculate p K a values of 21.2 and 23.1. The greater C(2)‐H acidity of the doubly bridged bis ‐propyl bis ‐imidazolium salt4 relative to10 may be attributed to the inductive or electrostatic destabilization of the conjugate acid dicationic azolium ion4 relative to the monocationic carbene9, which is enhanced by bis ‐tethering. Formation of tetraazafulvalene1 was not observed under the aqueous conditions employed highlighting that carbene reprotonation significantly outcompetesdimerization under these conditions. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Reaction of a bis ‐propyl bis ‐imidazolium di‐iodide salt in buffered D2 O solution gave complete deuterium exchange with no competing dimerization. The second‐order rate constant for deuteroxide‐ion catalyst exchange was used to estimate a carbon acid C(2)‐H p Ka value of 21.2.